2022
DOI: 10.1039/d2fo02718f
|View full text |Cite
|
Sign up to set email alerts
|

Co-encapsulation of quercetin and resveratrol in zein/carboxymethyl cellulose nanoparticles: characterization, stability and in vitro digestion

Abstract: Oral administration of combinations of specific nutrients and nutraceuticals can provide synergistic health benefits to humans. In this work, zein/carboxymethyl cellulose composite nanoparticles were successfully prepared using antisolvent precipitation methods....

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(1 citation statement)
references
References 52 publications
1
0
0
Order By: Relevance
“…This may be due to the presence of hydroxyl groups on Cur [38], allowing polyphenols to form hydrogen bonds with proteins, which is consistent with previous research results [11]. Proteins and polyphenols form covalent bonds (hydrogen bonds and hydrophobic interactions) [39]. When Dio and Cur were co-encapsulated into zein-SPI NPs, it could be seen that the intensity of their amide II bond peaks became lower, which also indicated that Cur was more hydrophobic than Dio, and the co-loading drug caused Cur to enter into a more hydrophobic microenvironment.…”
Section: Ftirsupporting
confidence: 90%
“…This may be due to the presence of hydroxyl groups on Cur [38], allowing polyphenols to form hydrogen bonds with proteins, which is consistent with previous research results [11]. Proteins and polyphenols form covalent bonds (hydrogen bonds and hydrophobic interactions) [39]. When Dio and Cur were co-encapsulated into zein-SPI NPs, it could be seen that the intensity of their amide II bond peaks became lower, which also indicated that Cur was more hydrophobic than Dio, and the co-loading drug caused Cur to enter into a more hydrophobic microenvironment.…”
Section: Ftirsupporting
confidence: 90%